Serum Vitamin Levels among Iraqi Cancer Patients Receiving Chemotherapy - Abdulrahman, Mohammed Salim; El-Yassin, Hedef D.; Al-Alwan, Nada. A. S. (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Cancers are an abnormal irregular growth of cells. There is an interaction between cancer cells, immune cells, and neurotransmitters with nutritional elements and vitamins. With the administration of chemotherapeutic agents, many studies have highlighted the importance of these interactions and the role of chemotherapeutic drugs in augmenting or ameliorating such changes. Therefore, early detection of vitamins level changes is vital to improve patients’ short-term outcome and quality of life. AIM: The aim was assessment of serum vitamins level changes in patients with cancer pre- and post-chemotherapy. MATERIALS AND METHODS: A cohort study was carried out on newly diagnosed patients with cancer in Al-Amal National Radiation Oncology Hospital/Baghdad/Iraq during the period from January 2019 to July 2019. Assessments of the studied samples were conducted as a baseline before receiving chemotherapy and after the third cycle of chemotherapy. Weight, height and body mass index (BMI) were measured for each subject enrolled in the study. Serum level of the following vitamins: A, B1, B2, B3, B6, B12, folic acid, D, and E was measured using ELISA technique. RESULTS: One Hundred patients who were diagnosed with different types of cancer were enrolled in this study. Seventy seven (77%) females and twenty three (23%) males. Mean age was 50.15 years ranged between (18-75) years old, BMI range (16-42). Serum vitamin levels that have shown a significant decrease post chemotherapy as compared with baseline were: A (0.64 ± 0.23 vs 0.64 ± 0.23, P=0.0003), E (19.47 ± 4.714 vs 14.70 ± 5.354, P<0.0001), B12 (366.0 ± 95.94 vs 291.1 ± 102.6, P<0.001), B9 (16.13 ± 4.13 vs 16.13 ± 4.13, P<0.0001) whereas vitamins B6 and D which showed lower than normal baseline level underwent significant increase after chemotherapy yet remained below normal (vitamin B6 4.19 ± 1.94 vs 8.22 ± 5.39; vitamin D 21.11 ± 7.21 vs 26.55 ± 15.22). CONCLUSION: Our findings highlight the importance of updating and tailoring our regimens to suit the changes of the nutritional elements and parameters of performance status of cancer patients in terms of outcome and patient satisfaction.